1990
DOI: 10.1111/j.1751-1097.1990.tb01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Uv Induced (6‐4) Photoproducts Are Distributed Differently Than Cyclobutane Dimers in Nucleosomes

Abstract: We have compared the distributions of two stable UV photoproducts in nucleosome core DNA at the single-nucleotide level using a T4 polymerase-exonuclease mapping procedure. The distribution of pyrimidine-pyrimidone (6-4) dimers was uncovered by reversing the major UV photo-product, cis-syn cyclobutane pyrimidine dimer, with E. coli DNA photolyase and photoreactivating light. Whereas the distribution of total UV photoproducts in nucleosome core DNA forms a striking 10.3 base periodic pattern, the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 38 publications
2
61
0
1
Order By: Relevance
“…1) (28). Also, CPDs tend to form away from the histone surface in UV-irradiated nucleosomes, chromatin, or intact human cells (23,25,39). Surprisingly, in this study we found that CTDs can adapt to different rotational settings as dictated by the TG motif (Figs.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…1) (28). Also, CPDs tend to form away from the histone surface in UV-irradiated nucleosomes, chromatin, or intact human cells (23,25,39). Surprisingly, in this study we found that CTDs can adapt to different rotational settings as dictated by the TG motif (Figs.…”
Section: Discussionmentioning
confidence: 43%
“…However, CPDs do not displace DNA from histones, and nucleosomes containing CPDs can be readily isolated or prepared (23,24). Furthermore, DNA interactions within nucleosomes do not significantly affect the overall frequency of CPD formation, because there is only an ϳ1.5-fold difference in CPD yield between linker DNA and DNA bound to nucleosomes (25,26). Rather, DNA interactions within nucleosomes affect the site of the lesion (23).…”
mentioning
confidence: 99%
“…The difference between the repair efficiencies for these lesions probably reflects the fact the (6-4)PPs are a better substrate for NER than are CPDs (10), most likely because they cause a greater distortion of the double helix structure, but also because of their preferential locations in the linker regions of nucleosomes (11). This is reminiscent of our previous observations in fetal human neurons, which, when kept in culture for several months, lost the ability to efficiently repair CPDs, but still dealt efficiently with (6-4)PPs (1).…”
Section: Ner Is Impaired At the Global Genomic Level Upon Macrophagementioning
confidence: 99%
“…On the one hand, packaging can protect DNA from damaging agents (22,23). On the other hand, it can hinder damage recognition and the access of repair machinery.…”
Section: Regions Repaired Later Are Associated With Higher Mutagenesismentioning
confidence: 99%